2006
DOI: 10.1590/s0037-86822006000100002
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos clínicos e epidemiológicos da epidemia de dengue no Recife, PE, em 2002

Abstract: RESUMO ABSTRACTThis paper shows data regarding dengue and hemorrhagic fever of the dengue epidemic in Recife in 2002 and the clinical, laboratorial and necropsy results from the 14 patients who died that year. The sorotype Den-3 was detected in 76.3% of cases. The majority of deaths occurred among men, over 20 years old, on the 11 th day of disease, attended in the private hospitals. The average values of the hematocryt and platelets were 40.7% and 56,313p/mm 3 , respectively. Hepatitis, with high levels of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
6

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 17 publications
0
11
0
6
Order By: Relevance
“…The hospital lethality rate due to DHF in Recife was 6.8%, with progression to death in around 11 days after the first symptoms 3 . This was close to the data found in the present study.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The hospital lethality rate due to DHF in Recife was 6.8%, with progression to death in around 11 days after the first symptoms 3 . This was close to the data found in the present study.…”
Section: Resultsmentioning
confidence: 97%
“…An epidemic in Recife showed that the most frequent location for hemorrhages was the digestive tract, followed by the nose and lungs 3 . The most frequent signs were ascites and pleural and pericardial effusion, with 71.4%, 57.1% and 28.6% respectively 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taxas elevadas também foram registradas no Estado de Pernambuco 14 e na capital, Recife-PE. 15 Os dados obtidos neste estudo mostram que as maiores incidências de casos de dengue coincidem com a estação chuvosa no Nordeste do Brasil, onde tem-se observado um padrão de sazonalidade da doença. Nos meses de maior precipitação pluvial, de fevereiro a junho, em todos os anos estudados, houve aumento na notificação de casos.…”
Section: Discussionunclassified